2016
DOI: 10.1158/1538-7445.am2016-3457
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3457: Social support as emotional adjustment determinant of breast cancer patients after surgery in selected hospitals in Nigeria

Abstract: Breast cancer is the most common invasive cancer and a leading cause of premature mortality for females worldwide. It accounts for 16% of all female cancers; 18.2% of all cancer deaths globally are from breast cancer. Social support plays a major role in modifying negative effect of this disease on affected individuals. It is an important psychosocial resource for coping with stressful life events. This study was carried out to examine social support as determinant of emotional adjustment of breast cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Though it has not been established scientifically, this kind of support has been revealed to increase the quality of life and help promote recovery and patients who have some sort of social support have quicker recovery and better survival [16]. In another study on the importance of social support in the management of breast cancer, it was revealed that such support had a significant effect on emotional adjustment of the patients after surgery as this often comes in form of family and friends who talk to and help the patients with personal problems [17]. This can be explained by the fact that these patients from such relationships and interactions develop resilience against the diseases while nurturing the feeling that they are not alone in the fight.…”
Section: Social and Institutional Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it has not been established scientifically, this kind of support has been revealed to increase the quality of life and help promote recovery and patients who have some sort of social support have quicker recovery and better survival [16]. In another study on the importance of social support in the management of breast cancer, it was revealed that such support had a significant effect on emotional adjustment of the patients after surgery as this often comes in form of family and friends who talk to and help the patients with personal problems [17]. This can be explained by the fact that these patients from such relationships and interactions develop resilience against the diseases while nurturing the feeling that they are not alone in the fight.…”
Section: Social and Institutional Supportmentioning
confidence: 99%
“…This institutional support more often than not comes from the church and herbal homes due to the belief that breast cancer is more spiritual than medical. In this kind of situation, the disease is viewed as caused by evil arrows from enemies and as such demands more for spiritual healing more than medical [17]. Unfortunately, when confronted with breast cancer, most women in Nigeria usually seek help from religious institutions more than medical attention, leading to late detection and a high mortality rate.…”
Section: Social and Institutional Supportmentioning
confidence: 99%
“…This kind of support has been revealed to increase the quality of life and help promote recovery and patients who have some sort of social support have quicker recovery and better survival" [15]. "In another study on the importance of social support in the management of breast cancer, it was revealed that such support had a significant effect on emotional adjustment of the patients after surgery as this often comes in form of family and friends who talk to and help the patients with personal problems" [16]. "This can be explained by the fact that these patients from such relationships and interactions develop resilience against the diseases while nurturing the feeling that they are not alone in the fight.…”
Section: Introductionmentioning
confidence: 99%